Coexistence of ferroelectricity and metallicity in M-doped BaTiO3 (M = Al, V, Cr, Fe, Ni, and Nb): First-principles study. (June 2021) - Li, Gang; He, Chen; Xiong, Ying; Zou, Zhi; Liu, Yulin; Chen, Qilai; Zhang, Wanli; Yan, Shaoan; Xiao, Yongguang; Tang, Minghua; Li, Zheng
Highlights: The ferroelectric and magnetic properties of metal atom (M) doped BaTiO3 (BTO) system were calculated by first-principles. Coexistence of ferroelectricity and metallicity in the Al-and Nb-doped BTO system. The ferroelectricity of an Al-doped BTO system is uncommonly enhanced. Coexistence of ferroelectric and ferromagnetic properties in Nb-doped BTO system. Abstract: Ferroelectric materials are typically insulators, but recent studies have shown that ferroelectric materials can be modified by design for the coexistence of metallicity and ferroelectricity. Here, by using first-principles calculations, we investigated ferroelectric, electronic, and magnetic properties of different metal atoms M doped BaTiO3 (BTO) (M=Al, V, Cr, Fe, Ni, and Nb) system with a doping concentration of 0.125. Our results indicate that electrons in Cr-, Fe-, Ni-, and V-doped BTO systems are highly localized in the doping atom and its nearby O atoms. Simultaneously, their ferroelectricity has not decreased much. However, ferroelectricity and metallicity can perfectly coexist in each unit cell of an Al-doped BTO system owing to its p -type conductivity that is nonmagnetic, which is predominantly contributed by p x /p y orbitals. Moreover, the ferroelectricity of an Al-doped BTO system is uncommonly enhanced. Besides, for a Nb-doped BTO system, the ferromagnetic n -type conductivity exists in each unit cell, and its ferroelectricity is reduced because of the existence of d xz /d yz orbital electrons that eliminate the out-of-plane electrical dipoles. Our results provide a new avenue to tune ferroelectric and ferromagnetic properties in multiferroic perovskites.